THE EFFECT OF TIME TOKEN LEARNING MODEL ON STUDENTS CRITICAL ABILITY IN SOCIAL STUDIES (GEOGRAPHY) (Harmony: Jurnal Pembelajaran IPS dan PKN, 2018)
Social Studies (Geography) learning still seems to have not achieved minimal completeness, among others, due to students learning less active. The method used in this study is the experimental method with Posttest only control design. The technique of collecting data is in the form of tests and documentation. Data analysis using normality test, homogeneity test and hypothesis test. The results of this study indicate that the experimental class treated with the time token learning model has an average value of 81.5 higher than the average of the control class treated with the lecture model getting a value of 63.81. This can be concluded that the time token learning model can improve critical thinking skills and the results of calculations on the T-test show that tcount> t table. where t count = 10.25 and t table = 1.67203. It means "There is the influence of the application of the time token learning model on students' critical thinking skills in social studies (Geography)" or the Ha hypothesis is accepted. Pembelajaran IPS (Geografi) masih telihat belum mencapai ketuntasan minimal, antara lain disebabkan dalam pembelajaran siswa terlihat kurang aktif. Metode yang digunakan dalam penelitian ini yaitu metode eksperimen dengan desain Posttest only control design. Teknik pengumpulan data berupa Tes dan Dokumentasi. Analisis data menggunakan Uji normalitas, uji homogenitas dan uji hipotesis. Hasil penelitian ini menunjukan bahwa kelas eksperimen yang diberi perlakuan dengan model pembelajaran time token memiliki memiliki nilai rata-rata sebesar 81,5 lebih tinggi dibandingkan dengan rata-rata kelas kontrol yang diberi perlakuan dengan model ceramah mendapatkan nilai yaitu 63,81. Hal ini dapat di simpulkan bahwa model pembelajaran time token dapat meningkatkan kemampuan berpikir kritis dan hasil perhitungan pada uji-T menunjukkan bahwa thitung > ttabel. yang mana thitung = 10,25 dan ttabel = 1,67203. Artinya â€œAda pengaruh penerapan model pembelajaran time token terhadap kemampuan berpikir kritis siswa pada mata pelajaran IPS (Geografi)â€ atau hipotesis Ha diterima.